Quality assesment of the program to detect breast cancer Tabasco 2018 - Hernández Vasconcelos, Juan Miguel; Santos Padrón, Hilda; Martínez Calvo, Silvia Isabel (Horizonte Sanitario, 2023)
Objective: To evaluate the quality of activities for the detection of breast cancer in the Strengthening Program for Medical Care in Tabasco in 2016.Materials and Method: A descriptive and retrospective research was carried out, through a documentary analysis using an ad hoc instrument, composed of (46 items) to evaluate the structure, processes and results, when executing the preventive activities of the Breast Cancer Program, included in the Strengthening Program to Medical Attention, operated by 13 Mobile Medical Units, in three municipalities of Tabasco during 2016.Results: In the structure was relevant the reduction in financing to operate the 13 Units, which contributed to the deterioration of activities, and although the number of operational personnel reached 84.62%, it lacked certified training on breast cancer; in the processes, the situational diagnosis was insufficient in 53.8%; the clinical breast examinations reached 25.69% of compliance in the target population, 19% in the teaching of clinical breast self-examination and the preparation of official records in 30.8% and in the results, user satisfaction was low (30.77%) and the impact of the program was not evaluated because it was not carried out in the period studied.Conclusions: The reduction in financing was considered as one of the main factors in the deterioration of the activities that for the detection of breast cancer, were carried out in the 13 Mobile Medical Units assigned to the Strengthening of Medical Care Program, which contributed to its low quality.Keywords: Program evaluation; Breast neoplasms; Prevention & control; Quality of health care.